2000
DOI: 10.1046/j.1469-7580.2000.19630347.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic oestrogen treatment are not selective for uterine noradrenaline‐containing sympathetic nerves: a transplantation study

Abstract: Previous studies have shown that chronic administration of oestrogen during postnatal rat development dramatically reduces the total content of noradrenaline in the uterine horn, abolishes myometrial noradrenergic innervation and reduces noradrenaline-fluorescence intensity of intrauterine perivascular nerve fibres. In the present study we analysed if this response is due to a direct and selective effect of oestrogen on the uterine noradrenaline-containing sympathetic nerves, using the in oculo transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…However, it can be suggested that the growth rate of cholinergic terminal fibers is affected by estrogen-induced changes in the target tissue. This possibility is supported by our recently reported intraocular transplantation studies showing that both estrogen (Brauer et al 2000a) and pregnancy (Brauer et al 1998) affect the receptivity of the myometrial tissue to sympathetic nerve fibers. Although the nature of the signals produced by the target has not yet been elucidated, it is possible that sex hormones affect the pattern of growth of uterine projecting neurons via changes in the production of target-derived neurotrophic factors (Thoenen 1995;Cowen and Gavazzi 1998;Gallo and Letourneau 1998;Naves et al 1998;Baloh et al 2000;Brauer et al 2000b,c;Varol et al 2000), changes in signals provided by the extracellular matrix (de Curtis 1991; Gavazzi et al 1995;Tessier-Lavigne and Goodman 1996), or changes in the receptivity of neurons to the signals produced by the target (Toran-Alleran 1996).…”
Section: Discussionsupporting
confidence: 72%
“…However, it can be suggested that the growth rate of cholinergic terminal fibers is affected by estrogen-induced changes in the target tissue. This possibility is supported by our recently reported intraocular transplantation studies showing that both estrogen (Brauer et al 2000a) and pregnancy (Brauer et al 1998) affect the receptivity of the myometrial tissue to sympathetic nerve fibers. Although the nature of the signals produced by the target has not yet been elucidated, it is possible that sex hormones affect the pattern of growth of uterine projecting neurons via changes in the production of target-derived neurotrophic factors (Thoenen 1995;Cowen and Gavazzi 1998;Gallo and Letourneau 1998;Naves et al 1998;Baloh et al 2000;Brauer et al 2000b,c;Varol et al 2000), changes in signals provided by the extracellular matrix (de Curtis 1991; Gavazzi et al 1995;Tessier-Lavigne and Goodman 1996), or changes in the receptivity of neurons to the signals produced by the target (Toran-Alleran 1996).…”
Section: Discussionsupporting
confidence: 72%
“…Although the contribution of progesterone to these changes remains uncertain, there is increasing evidence that oestrogen is a key factor in the remodelling of uterine sympathetic nerves in the non-pregnant female (Brauer et al 1995(Brauer et al , 1999). In addition, recent studies indicate that oestrogen-induced responses in the sympathetic innervation are mediated by changes in the target uterine tissue (Brauer et al 2000a;Krizsan-Agbas and Smith 2000).…”
Section: Introductionmentioning
confidence: 95%
“…To address this question, we have evaluated the sympathetic innervation of the uterus following chronic oestrogen treatment of infantile/prepubertal and young adult intact and ovariectomised rats. To examine whether the age of the neurons or the degree of development of the uterus determine the responsiveness of nerves to oestrogen, we have assessed the effects of oestrogen on the sympathetic reinnervation of intraocular transplants of young adult uterine myometrium into ovariectomised adult host rats (Brauer et al 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…When myometrium is transplanted to the anterior chamber of the eye of OVX female rats, chronic estrogen treatment prevents iridal sympathetic nerves from sprouting into the transplanted tissue, while resident iris innervation is apparently unaffected (Brauer et al 2000). Similarly, myometrial explants cocultured in vitro with pieces of superior cervical sympathetic ganglion lose their ability to promote neurite outgrowth if the explants are exposed to E2 in vivo or in vitro (KrizsanAgbas and Smith, submitted), indicating that estrogen can act directly to suppress the myometrium's neuritogenic properties.…”
Section: Introductionmentioning
confidence: 99%